2017
DOI: 10.1038/modpathol.2017.30
|View full text |Cite
|
Sign up to set email alerts
|

Central pathology review with two-stage quality assurance for pathological response after neoadjuvant chemotherapy in the ARTemis Trial

Abstract: The ARTemis Trial tested standard neoadjuvant chemotherapy (NAC) ± Bevacizumab (Bev) in the treatment of HER2 negative early breast cancer. We compare data from central pathology review with report-review and also the reporting behaviour of the two central pathologists.800 women with HER2-negative early invasive breast cancer were recruited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…The primary endpoint was pCR (absence of invasive cancer in both the breast and lymph nodes). Here, whether a pCR had occurred was either determined based on central pathology review or, where central review was not possible, on histopathology reports [ 6 ]. Details of eligibility and follow-up procedures are provided in the main trial report [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…The primary endpoint was pCR (absence of invasive cancer in both the breast and lymph nodes). Here, whether a pCR had occurred was either determined based on central pathology review or, where central review was not possible, on histopathology reports [ 6 ]. Details of eligibility and follow-up procedures are provided in the main trial report [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…There is also a lack of precise definitions on the degree of pathologic response, including major pathologic response (MPR) or complete pathologic response (CPR). In other cancers such as osteosarcoma [1][2][3] and breast, [4][5][6][7][8] colorectal, [9][10][11] and esophageal carcinomas, 12,13 there have been multiple studies investigating pathologic assessment of the effects of neoadjuvant therapy, including some detailed recommendations on how to handle these specimens. [14][15][16][17] A comprehensive mapping approach to gross and histologic processing of osteosarcomas after induction therapy has been used for over 40 years.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst early clinical trials showed a drop in proportion of cases classified as pCR following central histology review compared with local reports (90), our own experience with the ARTEMIS trial showed excellent agreement between source laboratory reports and central review with respect to pCR (91). However, in an audit of local pathology reports as part of the trial, only 45% of reports included an assessment of tumour response in the breast, dropping to 30% for response in the axillary lymph nodes (92).…”
Section: Assessing Responsementioning
confidence: 85%
“…The RCB is presently the most widely used system and will be described in more detail; it has been well validated, is simple and reproducible (91,102,103), and shows a strong association with survival outcomes across all molecular subtypes. As a result the RCB has been incorporated in the soon to be released International Collaboration on Cancer Reporting (ICCR) minimum dataset for breast pathology reporting post NACT.…”
Section: Residual Cancer Burdenmentioning
confidence: 99%